Sa Nagmamahal - Monteseña, Francisco Arias (Likhaan: The Journal of Contemporary Philippine Literature; Vol 16 No 2 (2022): Dx Machina: Philippine Literature in the Time of COVID-19, 2024)
These poems show the current situation of an ordinary Filipino amid the rising prices of fuel and commodities. It shows a picture of how we are coping with the situation.